Baffling Narrators: Barthes’s Neutral in Novels by Szabo, Sebastian, and Sebald - Kernaghan, Stephen Dimitrios Kerkinos (My University, 2018)
This essay uses Roland Barthes’s concept of the Neutral to explore the narrative styles of three 20th century European novels: The Door by Magda Szabo, For Two Thousand Years by Mihail Sebastian, and The Rings of Saturn by W.G. Sebald. In each case, the essay locates some unwillingness on the part of the narrator to make affirmations about himself or herself or the world, or an effort to baffle others’ attempts to do so. Given that each of these novels, to varying degrees, deals with the persecution of Jewish people in mid-century Europe, the essay tests the limits of the Neutral as a narrative impulse.
Thesis (Master's)--University of Washington, 2018
Keywords: Neutral; Creative writing; English